Optimizing Symmetry after Unilateral Mastectomy and Reconstruction with a Less Form-stable Prepectoral Implant - Jean-Claude D. Schwartz, MD, PhD; Michael Binstock, MS, PA-C (Plastic and Reconstructive Surgery, Global Open, 2021)
Summary:. Implant-based breast reconstruction after bilateral mastectomy allows for excellent symmetry between the reconstructed breasts. After unilateral mastectomy, it is difficult to achieve symmetry between the reconstructed and native breast. In the past, anatomical implants provided a reconstruction that more closely resembled the shape of a native breast compared with the cohesive, round subpectoral implants commonly placed today. Here, we describe the use of a less form-stable round implant placed in the prepectoral plane after mastectomy which provides improved symmetry with the contralateral native breast.